Magnetically Guided Catheters, Micro- and Nanorobots for Spinal Cord Stimulation - Torlakcik, Harun; Sarica, Can; Bayer, Patrick; Yamamoto, Kazuaki; Iorio-Morin, Christian; Hodaie, Mojgan; Kalia, Suneil K.; Neimat, Joseph S.; Hernesniemi, Juha; Bhatia, Anuj; Nelson, Bradley J.; Pané, Salvador; et al. (Frontiers in Neurorobotics, 2021)
Spinal cord stimulation (SCS) is an established treatment for refractory pain syndromes and has recently been applied to improve locomotion. Several technical challenges are faced by surgeons during SCS lead implantatio, particularly in the confined dorsal epidural spaces in patients with spinal degenerative disease, scarring and while targeting challenging structures such as the dorsal root ganglion. Magnetic navigation systems (MNS) represent a novel technology that uses externally placed magnets to precisely steer tethered and untethered devices. This innovation offers several benefits for SCS electrode placement, including enhanced navigation control during tip placement, and the ability to position and reposition the lead in an outpatient setting. Here, we describe the challenges of SCS implant surgery and how MNS can be used to overcome these hurdles. In addition to tethered electrode steering, we discuss the navigation of untethered micro- and nanorobots for wireless and remote neuromodulation. The use of these small-scale devices can potentially change the current standard of practice by omitting the need for electrode and pulse generator implantation or replacement. Open questions include whether small-scale robots can generate an electrical field sufficient to activate neuronal tissue, as well as testing precise navigation, placement, anchoring, and biodegradation of micro- and nanorobots in the in vivo environment.